Corruption, anti-corruption, vigilance, and state building from early to late modern times
1 online resource.
Keywords: "Corruption, Anti-Corruption, Vigilance, and State Building from Early to Late Modern Times challenges current historiographical approaches, proposing new interpretations to rethink the relation between corruption and the socio-political and economic transformations since early globalisation. Building on the latest research and offering new methods of inquiry, this book is a compelling resource for academics interested in political history and the history of corruption"--